Sustained attention variation monitoring through EEG effective connectivity. (July 2022) - Francisco-Vicencio, Manuel A.; Góngora-Rivera, Fernando; Ortiz-Jiménez, Xóchitl; Martinez-Peon, Dulce
Highlights: We presented a noninvasive tool EEG based to measure sustained attention using brain connectivity through the directed Direct Transfer Function (dDTF). We presented a noninvasive tool EEG based to measure sustained attention. We use brain connectivity through the directed Direct Transfer Function (dDTF) The prefrontal, right parietal, and visual cortex on both sides have the most relevant activity These results coincide with previous studies that are invasive and at a higher cost Abstract: Different cognitive models have been created through the last decades to identify the functional building blocks of attention, understand it, and develop tools and strategies to rehabilitate it. The sustained attention component, defined as the ability to pay attention to a stimulus for long periods of time is assessed in this work through an analysis of effective connectivity to uncover the dynamics between its component brain regions (in the right prefrontal and parietal cortices) in healthy volunteers. We applied a continuous performance test (CPT-AX) to measure the components of attention to 30 healthy young adults, to compute the indicators of sustained attention, and to obtain electroencephalography (EEG) data. We analyze the dynamics on the EEG activity of the CPT-AX and a resting state, through the directed Direct Transfer Function (dDTF) to assess the direct measures of connectivity and information flow between pairs of electrodes, which uncovered persistent and shorter ranges of electrical activity than previously found in the θ, α, and β bands at 4–5 Hz, 10–12 Hz, and 18–20 Hz respectively. Our findings show the dominance of effective connections going from the prefrontal cortex towards the right parietal lobe at 4 Hz, and 12 Hz to be predominant in visual cortex on both states. The tool developed with low-cost neuroimaging technologies provides an affordable way to assess other cognitive processes and states, and that can be further explored for real-time monitoring of the attention paid to a rehabilitation session or a lecture in a classroom setting.